Differences in the Employment Rate of Mothers Bringing Up a Child with a Disability and without Disabilities Źródło - Banaszkiewicz, Dorota; Komorowska, Olga; Kozłowski, Arkadiusz (Studia Oeconomica Posnaniensia, 2019)
The aim of the article is to compare the rate of employment and factors affecting it in a group of mothers raising children with and without disabilities. The analysis was based on the results of previous research carried out by various research centers, as well as on unit data from the Household Budget Survey 2014. The hypothesis formulated by the authors of the article is as follows: the rate of employment of mothers bringing up a child with a disability is lower than the rate of employment of mothers raising a child without a disability, both in general terms and in each group, separated according to the typical socio-demographic characteristics of the mother. The birth of a child in a family changes its functioning and enforces at least a temporary reduction of work usually by the mother. However, life with a child with disabilities places parents ahead of additional unexpected and time-sensitive, physical and financial challenges, which makes the professional activity of mothers more difficult in this group than in the group of mothers who look after children without disabilities. For women bringing up a child with a disability, work also acquires a therapeutic significance, because it makes for the possibility to detach from the child's disability and take a distance from her life.